Protokol HTTPS, Apakah Benar-benar Aman? - Deddy Prayama; Yuhefizar; Amelia Yolanda (Indonesian Society of Applied Science, 2021)
In particular, the method used in this research is a case study where previously the p3m.pnp.ac.id website still uses the http protocol. However http protocol does not have a method of securing data in its communication. The final result of this research is the design and implementation of the https protocol for data communication security that occurs between visitors and the p3m.pnp.ac.id website. The https protocol that has been implemented is tested to ensure the data traffic on the p3m.pnp.ac.id website is guaranteed to be safe and protected from possible piracy and data theft.